Diseño de un sistema integrado de gestión QHSE para el proceso de recolección de residuos sólidos en la Empresa de Servicios Públicos de Tocancipá S.A. ESP. (2014)
To carry out our degree work, it was necessary to specify the prior knowledge of the regulations apprehended during the course of the specialization, the extensive application of the ISO 9001, ISO 14001 and OHSAS 18001 standards, the knowledge of the company to work and the subsequent application of all the above in an integral way. The implementation of management systems in companies has highlighted the need to seek an effective integration of such systems that provides benefits and saves effort. In this work, dealing with the planning of the system provides us with an integrated management system model consistent with the methodological approaches found in the scientific literature and process-based management approach as a fundamental pillar. At present, many organizations have decided to address the management of certain areas of management through the application of recognized national and / or international standards, facilitating the provision of a structure and a clear rationale for how to carry out such management. Quality, the environment and health and safety at work are some of the management areas where the application of this type of standards has proliferated the most. In these areas, the standards to be applied in the company "Tocancipá public services company" are the ISO 9001: 2008 in quality management, the ISO 14001: 2004 in environmental management and the OHSAS 18001 standard: 2007 for the management of health and safety at work, it should be noted that the company at this time alone, is certified to the 9001: 2008 quality management and is in the process of recertification of the same. Within the review several shortcomings were found regarding the process map or organization chart, it would be prudent to have a look and reorganization, the charges are not very defined, that is to say in some occasions people have positions for which they do not have the expertise for the work to be done, or there are no charges that are important, for example the company does not have a QHSE coordinator, the characterization is not complete and does not cover the company's policy, in conclusion all the processes ocan to quality, the possible reason is because it does not yet have an integrated system, and it is not foreseen to be able to create a policy integrating all integral management systems, several risks were found that affect the health of people and their safety and several procedures not created, therefore with the realization of this work is intended not only to show the university that we can perform an integrated management process but to show the company what was reviewed, evaluated and with the solutions or probabilities of improvement, for the welfare of people, processes or activities and the company in general.